Deep Learning for Photonic Design and Analysis: Principles and Applications - Duan, Bing; Wu, Bei; Chen, Jin-hui; Chen, Huanyang; Yang, Da-Quan (Frontiers in Materials, 2022)
Innovative techniques play important roles in photonic structure design and complex optical data analysis. As a branch of machine learning, deep learning can automatically reveal the inherent connections behind the data by using hierarchically structured layers, which has found broad applications in photonics. In this paper, we review the recent advances of deep learning for the photonic structure design and optical data analysis, which is based on the two major learning paradigms of supervised learning and unsupervised learning. In addition, the optical neural networks with high parallelism and low energy consuming are also highlighted as novel computing architectures. The challenges and perspectives of this flourishing research field are discussed.